Social work students' perceptions of obesity. Issue 3 (3rd April 2019) - Lawrence, Shawn A.; Abel, Eileen Mazur; Stewart, Chris; Dziuban, Charles
ABSTRACT: Research indicates that mental health and medical professionals often hold negative views of overweight or obese people. Little is known about weight prejudice among social work students. In order to address this gap in the literature, this study examines the attitudes of Bachelor of social work and Master of social work students ( n  = 250) toward persons who are overweight and/or obese. Consistent with the literature, findings indicate generally those with higher body mass index scores are more likely to believe that obesity is beyond their control. Further, although age was correlated with Beliefs About Obese People scores, it was not a significant predictor. Implications for social work social justice and cultural competency curriculum are discussed.